2014
DOI: 10.1016/j.febslet.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

PML tumour suppression and beyond: Therapeutic implications

Abstract: a b s t r a c tRecognition of the tumour suppressive capacity of the Promyelocytic Leukemia protein (PML) has emerged beyond its identification through APL, to a broad spectrum of tumors. This ability has chiefly been linked to its role as a core component of dynamic structures termed PML Nuclear Bodies (PML-NBs). In response to a variety of stresses, key factors and their molecular modifiers are recruited to PML-NBs, where activating modifications are facilitated, leading to a cellular stress response. PML wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 102 publications
1
16
0
Order By: Relevance
“…Overall, these studies are in agreement with PML’s widely reported function as a tumour suppressor in a variety of both haematopoietic and solid tumours (Gamell et al 2014 ), however, chronic myeloid leukaemia (CML) is an exception to this. CML is a myeloproliferative disorder that, in common with APL, is characterised by a specific chromosomal translocation, in this case t(9;22), which gives rise to the tyrosine kinase BCR-ABL.…”
Section: Trim19supporting
confidence: 88%
“…Overall, these studies are in agreement with PML’s widely reported function as a tumour suppressor in a variety of both haematopoietic and solid tumours (Gamell et al 2014 ), however, chronic myeloid leukaemia (CML) is an exception to this. CML is a myeloproliferative disorder that, in common with APL, is characterised by a specific chromosomal translocation, in this case t(9;22), which gives rise to the tyrosine kinase BCR-ABL.…”
Section: Trim19supporting
confidence: 88%
“…Functional assays in mice expressing PML but lacking PML NBs showed impaired homologous recombination (HR) and non-homologous end-joining repair pathways, with defective localization of Brca1 and Rad51 to sites of DNA damage ( 89 ). Thus, although the physiological function of PML and the nuclear bodies have not been thoroughly elucidated, their tumor-suppressive role by supporting DNA damage response pathways may be common to all of these potential functions ( 19 , 89 ).…”
Section: Tumor Suppressor and Oncogenic Functions Of Pmlmentioning
confidence: 99%
“…A better understanding of the biophysical and biochemical mechanisms by which PML and/or the PML nuclear bodies participate in genome maintenance is expected to facilitate the development of therapeutic strategies for the treatment of PML-related diseases ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Promyelocytic leukemia protein (PML), also named TRIM19, belongs to the tripartite motif family (TRIM) of proteins that contain a RING finger, two B-boxes, and an α-helical coiled-coil (RBCC) domain [ 9 , 10 ]. As a major component of PML nuclear bodies (NBs) (also known as nuclear domain 10) [ 11 ], PML is involved in diverse cellular processes, including proliferation, apoptosis, gene transcription, and DNA damage response [ 12 14 ]. PML expression is increased by IFNs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%